Gas exchange, photochemical efficiency and growth of hydroponic okra under salt stress and salicylic acid - Mendonça, Allysson Jonhnny Torres (2024)
Okra (Abelmoschus esculentus L.) is a shrub belonging to the Malvaceae family, which stands out for its rusticity and adaptation to soil and climatic conditions, being cultivated by small farmers, especially in the semi-arid region of Northeast Brazil. In this context, the objective of this study was to evaluate the effect of foliar application of salicylic acid as an attenuator of salt stress on leaf gas exchange, photochemical efficiency, and growth of okra cv. Canindé in a hydroponic system. The experiment was carried out using a Nutrient Film Technique - NFT hydroponic system in a greenhouse, in Pombal, PB, Brazil, from January to March 2022, in a completely randomized design, in a split-plot scheme, with the four levels of electrical conductivity of the nutrient solution - ECns (3.0, 5.0, 7.0, and 9.0 dS m-1) considered as plots and four concentrations of salicylic acid – SA (0, 1.2, 2.4, and 3.6 mM) considered as subplots, with three replicates and two plants per plot. Increase in ECns levels from 3.0 dS m-1 inhibited leaf gas exchange, photochemical efficiency, and growth of okra cv. Canindé in hydroponic cultivation, at 34 days after transplanting. Foliar application of SA at concentrations of 2.2 and 1.5 mM promoted increments in stomatal conductance and transpiration, respectively. Salicylic acid at concentration of 1.9 mM associated with saline nutrient solution of 9.0 dS m-1 increased the variable fluorescence of okra plants cv. Canindé, at 34 days after transplantation.